PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, DAN PERILAKU KEUANGAN TERHADAP MINAT PENGGUNAAN DIGITAL FINANCE PADA UMKM DI KOTA BATAM - Jackie Lee Lee; Handra Tipa (SCIENTIA JOURNAL, 2026)
The rapid development of digital-based financial services is driving changes in the financial management patterns of Micro, Small, and Medium Enterprises (MSMEs) in Batam City, thus demanding readiness in terms of financial literacy, access, and behavior. This study aims to analyze the influence of financial literacy, financial inclusion, and financial behavior on the interest in using digital finance among MSMEs in Batam City. The study used a quantitative approach with a population of 2,179 MSMEs operating in Batam City, with a purposive sampling technique of 100 respondents obtained using the Slovin formula. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the multiple linear regression analysis indicate that financial literacy influences the interest in using digital finance with a contribution of 25.4%, financial inclusion has an influence of 37.9%, and financial behavior has an influence of 60.9%. The analysis of the coefficient of determination (R2) can show that financial literacy, financial inclusion, and financial behavior are able to explain 88.2% of the variation in interest in using digital finance in MSMEs in Batam City, and the results of the t-test and F-test prove that financial literacy, financial inclusion, and financial behavior have a significant influence both partially and simultaneously on interest in using digital finance.